Pengaruh Motivasi Kerja, Quality Of Work Life, Dan Kepuasan Kerja Terhadap Kinerja Guru MAN Kota Malang - Burhan Rizky Pratama, Burhan; Wahidmurni, Wahidmurni; Harini, Sri (Jurnal Ilmiah Global Education, 2024)
Optimal human resource management is a form of MAN's goal in carrying out its activities effectively and efficiently. The importance of teacher motivation, fulfilling the quality of work life in the work environment, and teachers feeling satisfied at work is a form of effort to optimize the potential and level of productivity of MAN's teacher resources. This type of research is a literature study, a theoretical study that describes the fulfillment of work motivation, quality of work life, and high job satisfaction that teachers have in a straight line according to MAN's expected work results.